Analisis Perbandingan Kinerja Pembangkit Listrik Tenaga Surya dan Pembangkit Listrik Tenaga Uap pada Lingkungan PT. RAPP - Satria Darmawan; Rahmaniar; Pristisal Wibowo (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
This study compares the performance of Solar Power Plants (PLTS) and Steam Power Plants (PLTU) at PT. RAPP. The methods used include daily energy production data collection, environmental observation, and statistical analysis to assess the efficiency and performance of both systems. The analysis reveals that PLTS has high efficiency in converting solar energy into electricity but experiences reduced efficiency due to module PV and inverter malfunctions in Phase 3. Meanwhile, the Dual Fuel Line 2 PLTU achieves a thermal efficiency of 43.24%, with biomass as the primary fuel, which reduces carbon emissions but still requires natural gas for stability. PLTS excels in environmental sustainability and lower operational costs, whereas PLTU offers more stable and substantial production capacity. Recommendations include repairing the PLTS system, expanding the project, investing in technology, and managing PLTU emissions for a more efficient and sustainable energy solution at PT. RAPP.